Alat Bukti Ganda Hak Garap Tanah Kelompok Tani Pada Areal Izin Pertambangan PT. Kaltim Prima Coal - Eli Tri Kursiswanti; Septhian Cahya Nugraha; Rusli Akib (LPPM STIH Awang Long, 2021)
Ownership of cultivation rights on the same land by several farmer groups in the mining permit area of ​​PT. Kaltim Prima Coal in Swarga Bara Village, North Sangatta District, East Kutai Regency, East Kalimantan, has created conflicts between community groups. The problem occurred because the official apparatus (Village Head and Camat) issued a certificate of cultivating land rights without a clear legal basis so that there was overlapping of arable land rights and gave rise to double evidence of cultivating rights on land on the same object/land. Based on these problems, this study examines the factors causing the double evidence of cultivation rights over the mining permit area of ​​PT. Kaltim Prima Coal in Swarga Bara Village, North Sangatta District, East Kutai Regency, East Kalimantan. In addition, to find out how the form of dispute resolution between fellow holders of cultivation rights over the mining permit area of ​​PT. Kaltim Prima Coal in Swarga Bara Village, North Sangatta District, East Kutai Regency, East Kalimantan so that the settlement can be beneficial for all parties to the dispute. The author uses the library research method or literature review. This literature review research is conducting research from library books, magazines, journals and articles and sources from the internet that are relevant to the problems discussed. The following is a study based on the Law of the Republic of Indonesia Number 5 of 1960 concerning Basic Agrarian Regulations or abbreviated as UUPA.